Quantification of Global DNA Methylation in Canine Mammary Gland Tumors via Immunostaining of 5-Methylcytosine: Histopathological and Clinical Correlations - Biondi, Luiz Roberto; Tedardi, Marcello Vannucci; Gentile, Luciana Boffoni; Chamas, Patricia Pereira Costa; Dagli, Maria Lucia Zaidan (Frontiers in Veterinary Science, 2021)
Mammary tumors are the most prevalent neoplasms in non-neutered female dogs, with genetic and epigenetic alterations contributing to canine mammary carcinogenesis. This study quantified global DNA methylation in 5-methylcytosine (5mC)-immunostained canine mammary tumor samples and established histopathological and clinical correlations. A total of 91 formalin-fixed paraffin-embedded mammary tumor samples from female dogs were retrospectively selected and subjected to immunohistochemistry using an anti-5mC mouse monoclonal antibody. We evaluated 5mC+ stained nuclei of neoplastic epithelial cells in canine mammary glands to obtain semiquantitative histoscores based on staining intensity. Survival rates were estimated based on owners’ or veterinary records. Histological samples comprised 28 and 63 benign and malignant canine mammary gland tumors, respectively. Results revealed significant differences between global DNA methylation patterns when mammary samples were categorized as benign or malignant (p = 0.024), with hypomethylated patterns more prevalent in malignant tumors and those with higher relapse behavior (p = 0.011). Of note, large diameter (> 5 cm) tumors revealed a lower methylation pattern (p = 0.028). Additionally, we found non-statistically significant differences when tumors were grouped by histopathological characteristics, clinical parameters, or survival. These findings propose global DNA methylation assessment as a promising tool for detecting canine mammary tumors with relapse propensity.